Budaya Islam sebagai Sistem Nilai Global Analisis Pemikiran Ali Ahmad Madkur - Azzimatul Hikmah; Sihab, Wahyu (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study is motivated by the increasing complexity of global culture, which demands a value system capable of providing direction and meaning in human life. In this context, Islam is viewed as having the potential to serve as a global value system through a cultural concept grounded in revelatory values. This study aims to analyze the concept of culture from an Islamic perspective as a global value system by examining the thought of Ali Ahmad Madkur. The method used is a qualitative approach based on a Systematic Literature Review (SLR), systematically and critically examining various relevant scientific literature. The results of the study indicate that Islamic culture in Madkur’s thought is built upon two main dimensions: the normative dimension, which is derived from the Qur’an and Sunnah, and the practical dimension as its actualization in social life. Although this approach has strengths in maintaining the integrity of values, it still faces challenges in responding to the complex, dynamic, and hybrid nature of global cultural dynamics. Therefore, a more integrative approach is needed to ensure that Islamic cultural values remain relevant and operational in a global context. This study has implications for strengthening more contextual studies of Islamic culture and developing Islamic education that is adaptive to the changing times.